TGFβ1 regulates HGF‐induced cell migration and hepatocyte growth factor receptor MET expression via C‐ets‐1 and miR‐128‐3p in basal‐like breast cancer. Issue 9 (30th July 2018) - Breunig, Christian; Erdem, Nese; Bott, Alexander; Greiwe, Julia F.; Reinz, Eileen; Bernhardt, Stephan; Giacomelli, Chiara; Wachter, Astrid; Kanthelhardt, Eva J.; Beißbarth, Tim; Vetter, Martina; Wiemann, Stefan
Abstract : Breast cancer is the most common cancer in women worldwide. The tumor microenvironment contributes to tumor progression by inducing cell dissemination from the primary tumor and metastasis. TGFβ signaling is involved in breast cancer progression and is specifically elevated during metastatic transformation in aggressive breast cancer. In this study, we performed genomewide correlation analysis of TGFBR2 expression in a panel of 51 breast cancer cell lines and identified that MET is coregulated with TGFBR2 . This correlation was confirmed at the protein level in breast cancer cell lines and human tumor tissues. Flow cytometric analysis of luminal and basal‐like breast cancer cell lines and examination of 801 tumor specimens from a prospective cohort of breast cancer patients using reverse phase protein arrays revealed that expression of TGFBR2 and MET is increased in basal‐like breast cancer cell lines, as well as in triple‐negative breast cancer tumor tissues, compared to other subtypes. Using real‐time cell analysis technology, we demonstrated that TGFβ1 triggered hepatocyte growth factor (HGF)‐induced and MET‐dependent migration in vitro . Bioinformatic analysis predicted that TGFβ1 induces expression of C‐ets‐1 as a candidate transcription factor regulating MET expression. Indeed, TGFβ1‐induced expression of ETS1 and breast cancer cell migration was blocked by knockdown of ETS1 . Further, we identified that MET is a direct target of miR‐128‐3p and that this miRNA is negatively regulated by TGFβ1. Overexpression of miR‐128‐3p reduced MET expression and abrogated HGF‐induced cell migration of invasive breast cancer cells. In conclusion, we have identified that TGFβ1 regulates HGF‐induced and MET‐mediated cell migration, through positive regulation of C‐ets‐1 and negative regulation of miR‐128‐3p expression in basal‐like breast cancer cell lines and in triple‐negative breast cancer tissue. Abstract : In the tumor microenvironment, TGFβ1 and HGF are secreted by tumor stromal cells. In the present report, we show that TGFβ1 regulates MET expression in breast cancer by upregulating C‐ets‐1 and downregulating miR‐128‐3p expression. C‐ets‐1‐mediated increases in the expression of MET and miR‐128‐3p directly target MET expression. In this way, TGFβ1 induces tumor cell migration in a HGF‐dependent manner.